Caring for Mexican-American Clients - Bette Ide (Online Journal of Rural Nursing and Health Care, 2005)
There are growing Mexican-American populations in rural areas. This editorial is a continuation of the previous column on communicating with those clients. Dr. Loretta Heuer, associate professor at the University of North Dakota, again offers suggestions to help rural nurses in caring for them. One major issue is the use of an interpreter. There are two styles of interpreting, line-by-line and summarizing. Line-by-line interpretation ensures accuracy but takes more time; one can only speak few sentences at a time and must use simple language, no medical jargon. Summarizing is faster and useful in teaching relatively simple health techniques with which the interpreter is already familiar.